Réponses

  • Utilisateur Brainly
2014-06-05T07:41:52+02:00
(12x90)+(-7)-(+89)-(-5/6)*56+6,7:(-9)=

(1080)-7+89 -140/3 - 6,7/9 =

1162 - 140/3 - 6,7/9 =

 100313/90
Meilleure réponse !
2014-06-05T08:00:13+02:00
(12 x 90) + (- 7) - (+ 89) - (-5/6) * 56 + 6,7 : (- 9)
= 1080 - 7 - 89 + 5/6 x 56 + 6,7 : - 9
= 100 - 7 - 89 + 280/6 + 6,7 x - 1/9
= 100 - 7 - 89 + 280/6 - 6/63
= 100 x 378 / 1 x 378 - 7 x 378 / 1 x 378 - 89 x 378 / 1 x 378 + 280 x 6 x 63 - 6 x 6 / 63 x 6
= 37800/378 - 2646/378 - 33642/378 + 1680/378 - 36/378
= 39480/378 - 36324/378
= 3156/378
= 6 x 526 / 6 x 63
= 526/63